Merangkul Produk Dalam Negeri: Implementasi Sila Ketiga Pancasila - Berchah Pitoewas, Berchah Pitoewas; Abdul Halim, Abdul Halim; Atika Fadiyah, Atika Fadiyah (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2025)
One of the practices of the third principle of Pancasila is to love local products. Embracing domestic products is in line with the principle of promoting inclusivity and mutual respect in Indonesia. The Indonesian economy is a dynamic and dynamic society characterized by ethnic, religious and cultural diversity. The Indonesian economy is an important contributor to the development of the country. A major contribution of the MSME sector is its ability to survive and improve performance even in the face of economic crises. By embracing and celebrating our cultural heritage in this way, we lay the foundation for a vibrant and thriving society that values ​​and cherishes its past while looking forward to a bright and promising future. Education and awareness campaigns to promote the importance of buying local and supporting local businesses can also play an important role in stimulating economic growth and sustainability. By educating the public about the positive impacts of choosing locally made goods and services, we can drive change towards a more sustainable and resilient economy.